The Silent Struggle : Exploring the impact of General Anxiety Disorder on Daily Life : A Case Report - Prasetya, Era Catur; Subagyo, Roni; Sudirman, Choiros Sirli (International Journal of Psychology and Health Science, 2025)
Generalized Anxiety Disorder is a common and disabling illness that is often underdiagnosed and undertreated, characterized by chronic, pervasive anxiety and worry accompanied by nonspecific physical and psychological symptoms including restlessness, fatigue, difficulty concentrating, irritability, muscle tension, and sleep disturbances. While anxiety can be an appropriate response to stressful situations, it is considered pathological when disabling and difficult to control. This case study, which aimed to explore generalized anxiety disorder and its management in patients, utilized diagnostic criteria from Pedoman Penggolongan dan Diagnosis Gangguan Jiwa-III and the Diagnostic and Statistical Manual of Mental Disorders-5, finding that the patient's manifestations aligned with established diagnostic criteria. Generalized anxiety disorder often goes undiagnosed and untreated due to accompanying physical complaints, requiring not only pharmacological interventions but also non-pharmacological approaches such as cognitive behavioral therapy to effectively control the patient's thought patterns.